Spatial Mapping of Protein Adsorption on Mesoporous Silica Nanoparticles by Stochastic Optical Reconstruction Microscopy - Clemments, Alden M. (J Am Chem Soc, 2017)
Exposure to biological fluid envelops a nanoparticle in layers of proteins and biomolecules, which has a profound impact on the nanoparticle’s biological fate. Although the identities and amounts of the proteins in this “corona” have been thoroughly examined, the spatial arrangement of the proteins is unclear, a problem that is compounded on porous nanoparticles due to penetration of proteins within the porous network. To address this problem, we have developed a procedure based on information derived from stochastic optical reconstruction microscopy. We employed a mathematical model to reveal the penetration depth of several proteins within porous nanoparticles. Understanding protein penetration depth provides an explanation for the composition of the protein corona, aiding in the development of safe and effective particle-based therapies.